2018
DOI: 10.1186/s12884-018-1887-x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D levels in an Australian and New Zealand cohort and the association with pregnancy outcome

Abstract: BackgroundPregnant women are at increased susceptibility to vitamin D deficiency. Hence, there is continuing interest in determining how vitamin D influences pregnancy health. We aimed to compare vitamin D status in two distinct populations of pregnant women in Australia and New Zealand and to investigate the relationship between vitamin D status and pregnancy outcome. This included evaluating possible effect measure modifications according to fetal sex.MethodsSerum 25-hydroxy vitamin D (25(OH)D) was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 52 publications
3
45
0
Order By: Relevance
“…It has been reported that estrogen may protect against vitamin D deficiency and that immune‐modulatory effects of vitamin D vary by sex, leading to the suggestion that males may be more susceptible to effects of vitamin D deficiency [Ali, Cui, Alexander, & Eyles, ; Cannell, ; Correale, Ysrraelit, & Gaitan, ]. An Australian study [Wilson et al, ] reported an interaction of fetal sex and gestational 25(OH)D on gestational diabetes mellitus, with female “pregnancies” showing an association in the unexpected direction, similar to our findings by sex. Other studies of environmental risk factors and ASD suggest sex‐specific effects [Kern et al, ; Lyall, Croen, Weiss, et al, ; Roberts et al, ; Schaafsma & Pfaff, ], but small numbers of affected females often limit the ability to study sex differences in ASD etiology.…”
Section: Discussionsupporting
confidence: 86%
“…It has been reported that estrogen may protect against vitamin D deficiency and that immune‐modulatory effects of vitamin D vary by sex, leading to the suggestion that males may be more susceptible to effects of vitamin D deficiency [Ali, Cui, Alexander, & Eyles, ; Cannell, ; Correale, Ysrraelit, & Gaitan, ]. An Australian study [Wilson et al, ] reported an interaction of fetal sex and gestational 25(OH)D on gestational diabetes mellitus, with female “pregnancies” showing an association in the unexpected direction, similar to our findings by sex. Other studies of environmental risk factors and ASD suggest sex‐specific effects [Kern et al, ; Lyall, Croen, Weiss, et al, ; Roberts et al, ; Schaafsma & Pfaff, ], but small numbers of affected females often limit the ability to study sex differences in ASD etiology.…”
Section: Discussionsupporting
confidence: 86%
“…A total of 1639 were excluded after reading titles and/or abstracts, and 75 articles were subjected to a full-text review. After reading the full text, a total of 24 cohorts were invited to participate, which included 13 cohort studies [27][28][29][30][31][32][33][34][35][36][37][38][39], seven case-control studies [40][41][42][43][44][45][46] and four cross-sectional studies [47][48][49][50].…”
Section: Search Resultsmentioning
confidence: 99%
“…Women working in an institutional setting, young women and living in winter are more prone to vitamin D de ciency due to reduced solar exposure. Decreased serum vitamin D levels among preconception fertile women may predispose to increased risk for adverse pregnancy [13,26]. Therefore, we propose that healthy fertile women who are pregnancy in following 3-6 months may be screened for serum 25…”
Section: Discussionmentioning
confidence: 99%
“…For the stepwise multiple linear regression analysis ( This is alarming as those women are planning to get pregnant because routine pre-conception check-up projects (Women receive routine pre-pregnancy check-up at 3-6 months before they became pregnant in China) do not include measurement of serum 25(OH)D. Several studies have described an association between insu ciency or de ciency in 25(OH)D levels and adverse pregnancy outcomes including gestational diabetes mellitus, preeclampsia, preterm delivery, recurrent abortion, and intrauterine growth restriction [24,25,26]. More recent data showed that preconception vitamin D status was associated with male live birth [27].…”
Section: General Characteristics Of Participant Womenmentioning
confidence: 99%